PELATIHAN DESAIN GRAFIS MENGGUNAKAN APLIKASI CORELDRAW PADA SISWI KELAS XI SMK IBRAHIMY 1 SUKOREJO - Alfiyah Aurella; Nafisatul Insiyah; Zaehol Fatah (Jurnal Padamu Negeri, 2025)
This community service activity took place at SMK Ibrahimy 1 Sukorejo which included learning about graphic design with a theme related to digital technology, namely graphic design training using the CorelDraw application, the aim of which was to increase students’ creativity in designing, withthe hope that later when they graduate the students can immediately work or open their own business space. The approach used in this training activity was a lecture delivering material about graphic design using the CorelDraw application, then practicum and closed with a question and answer session. CorelDraw Software was used as a tool in this activity because it is easy to master for new users who want to learn to design a design. The output of this activity is that students are able to create a logo design, poster, and banner.